Penerapan Asas Kepastian Hukum dalam Penyelesaian Sengketa Tumpang Tindih Sertipikat Hak Milik atas Tanah (Studi Kasus Putusan Nomor 2/G/2023/PTUN.PLK) - Musmuliadi, Musmuliadi; Gaol, Selamat Lumban; Sudarto, Sudarto (FOCUS, 2025)
The land registration system has been regulated in government regulation Number 24 of 1997 to guarantee legal certainty of land ownership, although the system is good, it turns out that there are still many land problems, especially regarding overlapping ownership. Overlapping ownership is caused by multiple land certificates issued by the BPN for one land object with multiple certificates due to inaccuracy in the land registration process or other elements carried out by the BPN (National Land Agency. The research method used is normative juridical/ The results of the research are the application of the principle of legal certainty in resolving disputes over overlapping land ownership certificates that the principle of legal certainty aims to provide a guarantee of clarity, justice, and legal protection to the disputing parties. In this case, the state through the National Land Agency (BPN) and the judiciary must ensure that the dispute resolution process is carried out fairly, transparently, and based on valid legal evidence. Land administration reform, data digitization, and increased supervision of certificate issuance are also important elements to prevent similar disputes in the future. Ratio decidendi Decision Decision Number 2/G/2023/PTUN.PLK regarding the dispute over overlapping certificates of ownership of land that the Plaintiffs suspect that the issuance of the certificate of the disputed object a quo did not go through a legal process, resulting in an overlap with their land and that of the late Hj. Nasuha. In the trial at the State Administrative Court (PTUN), the judge will assess whether the administrative decision that gave birth to the certificate of the disputed object a quo has met the legal requirements. The judge will examine the legal basis for the issuance of the certificate, the validity of the procedures carried out, and the impact of the issuance of the certificate on the rights of the Plaintiffs.